Improvement of growth and nutrient uptake of upland rice grown on degraded acid soil with the application of liquid organic fertilizer - Barus, Junita; Endriani; Mustikawati, Dewi Rumbaina; Meithasari, Dian; Ernawati, Rr; Wardani, Nila; Tambunan, Reny Debora; Silalahi, Marsudin; Slameto (Brawijaya University, 2024)
This research aimed to determine the effectiveness of several types of liquid organic fertilizer (LOF) derived from plant waste and the dose of P fertilizer on the growth and yield of upland rice on degraded acid soil. The treatments consisted of two factors. The first factor (A) was several types of LOF consisting of A1 (control), A2 (LOF containing isolates of P-solubilizing bacteria), A3 (LOF-banana waste), and A4 (A2+A3). The second factor (B) was fertilizer doses consisting of B1 (50% of the recommended dose of P fertilizer), B2 (75% of the recommended dose of P fertilizer), and B3 (100% of the recommended dose of P fertilizer). The treatment combinations were arranged in a factorial randomized block design with three replications. The research results showed that applying either LOF-banana waste or the mixture of LOF-banana waste and LOF-containing isolates of P-solubilizing bacteria improved plant height, the number of tillers, and N and P uptake by the plant. The rice grain yields among the treatments were not significantly different, but the highest rice grain yield (139.8 g/pot) was obtained at the treatment of the mixture of LOF-P isolate + LOF-banana waste (A2+A3 treatments). The 75% of the recommended dose of P fertilizer was not significantly different from 100% P fertilizer with LOF on growth and yield upland rice and nutrient uptake by the plant.